Impaired learning from punishment of errors in smokers: Differences in dorsolateral prefrontal cortex and sensorimotor cortex blood-oxygen-level dependent responses - Duehlmeyer, Leonie (Neuroimage Clin, 2019)
Cigarette smokers have shown hypersensitivity to reward and hyposensitivity to punishment, along with impairments in learning from errors. The underlying neural mechanism for this failure to adapt performance following an error, particularly when receiving negative feedback, are unclear. Smokers were hypothesized to have poorer error-learning following monetary punishment, associated with hypoactivation in the insula, dorsal anterior cingulate, and hippocampal cortical regions. Twenty-three smokers (8 females, mean age = 25.48, SD = 4.46) and twenty-three healthy controls (13 females, mean age = 24.83, SD = 5.99) were administered an associative learning task, providing monetary reward and punishment for recall performance, during fMRI data collection. Compared with controls, smokers had a lower error-correction rate and were less sensitive to punishment magnitude. Hyperactivity during recall was independent of future error correction, but smokers' successful re-encoding appeared related to higher dorsolateral prefrontal cortex activity while controls had equivalent activation for corrected and repeated errors. While controls showed higher deactivation of the sensorimotor cortex during high punishment, smokers showed higher deactivation during low punishment. The present results support smokers having poorer learning from errors and decreased attentional control associated with hyperactivity in the dorsolateral prefrontal cortex. Additionally, smokers exhibited decreased punishment sensitivity that appeared to limit their ability to adapt learning in the face of repeated negative feedback.